Microshear bond strength evaluation of surface pretreated zirconia ceramics bonded to dentin - Anand, Shenbagakuttalam; Ebenezar, Ambrose Vedamanickam Rajesh; Anand, Nirupa; Rajkumar, Kothandaraman; Mahalaxmi, Sekar; Srinivasan, Narasimhan (European Journal of Dentistry, 2015)
Objectives: To comparatively assess the micro shear bond strength (MSBS) of dentin bonded surface pre-treated zirconia ceramics. Materials and Methods: Zirconia blocks were sectioned into 50 cubical blocks. The blocks were further categorized into five groups (n = 10 each). Group I: No treatment was performed on zirconia samples; Group II: The zirconia samples were sand-blasted; Group III: Group II + etched with 9.8% of hydrofluoric (HF) acid for 60 s; Group IV: The sandblasted zirconia samples were selectively infiltrated with low fusing porcelain; and Group V: Group IV + etched using 9.8% HF acid gel. The zirconia specimens were then bonded to dentin samples, and the samples were tested for MSBS evaluation using universal testing machine. Results: The MSBS of all the four experimental groups shows greater value than group I. Among the experimental groups, group V and group IV do not show any statistical significant difference, whereas the mean MSBS of groups IV and V were statistically greater than group III and group II. However, groups I, II, and III do not show any statistical significant difference in mean MSBS values between them. Conclusion: Selective infiltration etching of zirconia ceramics provides the highest bond strength with resin cement.
Keywords: Hydrofluoric acid etching; sandblasting; selective infiltration etching; Zirconia blocks